Digitalizing the College of Architecture Museum - Lopez, Karen Therese F. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 10, 2023)
Museums are an accessible means of exposing students to excellent architectural works. Such immersion is important to inspire and enhance the skills of architects and aspiring architects. One such museum is Haraya, an architecture museum that transformed from a physical exhibition to a fully digital one because of the pandemic. This study explored how a university digital museum was created in a feasible manner, with the objective of making the experience similar to the physical museum. This required data gathering, exploring options, and creating a new digital museum for Haraya. We created Haraya 2022 using a 3D model, rendered images, rendered videos, links, and navigational nodes. It was made available for online viewing to the public. A survey was also conducted to determine the viewers’ satisfaction with the Haraya 2022 digital museum. The results showed positive feedback where most had an excellent or a very good experience. However, there were navigational issues that needs to be resolved for future digital museums. The method used to make Haraya 2022 is a viable option for digital museums. If a physical museum is present, a digital counterpart can still be made for better accessibility.